Long-Term Follow-Up after Prostatectomy for Prostate Cancer and the Need for Active Monitoring. (10th March 2020) - Swanson, Gregory P.; Chen, Wencong; Trevathan, Sean; Hermans, Michael
Abstract : Background . Only truly long-term follow-up can determine the ultimate outcome in prostate cancer. Most studies have a median follow-up of less than 10 years and then project outcomes out to 15 and 20 years. We sought to follow patients for at least 20 years. Materials and Methods . We followed 754 prostate cancer patients treated with radical prostatectomy from 1988 to 1995 for a median follow-up (in survivors) of 23.9 years. We excluded lymph node and seminal vesicle positive patients and an additional 47 patients that did not have baseline prostate-specific antigen (PSA). This left 581 patients for analysis. Results . With the factors of PSA, Gleason score, and extraprostatic extension/margin positivity, we could partition patients into three risk groups for biochemical failure (low, intermediate, and high). In further analysis, we found that the risk of metastatic disease in the first two groups was almost identical (4% and 5%, respectively), while it was 19% in the high-risk group. High-risk patients were those with PSA >20 ng/ml and/or Gleason >7, or Gleason 7 + PSA 10–20 + epe (and or margin) positive. They had a 22% prostate cancer mortality. Conclusion . In patients with truly long-term follow-up after prostatectomy for prostate cancer, the risk of metastatic disease and cancer death is very low. Patients with the lower risk findings do not appear to benefit from routine follow-up after 10 years free of biochemical recurrence. With a higher risk of later failure, we recommend that the higher risk patients be followed at least intermittently for another 5 years (out to 15 years).